Topical diclofenac therapy for osteoarthritis: a meta-analysis of randomized controlled trials. Issue 5 (May 2016) - Deng, Zhen-han; Zeng, Chao; Yang, Ye; Li, Yu-sheng; Wei, Jie; Yang, Tuo; Li, Hui; Lei, Guang-hua
Abstract The objective of this study was to evaluate the efficacy and safety of topical diclofenac therapy for osteoarthritis (OA). A meta-analysis of randomized controlled trials was conducted. A comprehensive literature search, covering the databases of Medline, the Cochrane Central Register of Controlled Trials, and EMBASE, was conducted in September 2014 to identify the randomized controlled trials which adopted the topical diclofenac therapy for OA. A total of nine papers were included in this meta-analysis. Topical diclofenac appears to be effective in both pain relief (standard mean differences (SMD) = 0.40; 95 % confidence interval (CI) 0.19 to 0.62;P  = 0.0003) and function improvement (SMD = 0.23; 95 % CI 0.03 to 0.43;P  = 0.03) when compared with the control group. The sensitivity analysis and subgroup analysis showed that the result of pain intensity was stable and reliable, while the result of physical function improvement was vague. With respect to safety, topical diclofenac demonstrated a higher incidence of adverse events such as dry skin, rash, dermatitis, neck pain, and withdrawal. Topical diclofenac is effective in pain relief as a treatment of OA. It may also have a potential effect in function improvement, which needs further studies to be explored. Although, some adverse effects were observed in the application of topical diclofenac, none of them was serious.